Understanding patient and caregiver perspectives using a dyad approach for data collection: A systematic review of the literature - Jane Loftus; Andrew Yaworsky; Diane Turner-Bowker; Andrew Palladino; Roger Lamoureux; Emily Love; Andreas Pleil (The Beryl Institute, 2022)
Treatments outside of a clinical setting may be managed independently by the pediatric patient, independently by a caregiver, or by the patient and caregiver together. Best practices for pediatric clinical outcome assessment (COA) recommend patient-reported outcome (PRO) and/or observer-reported outcome (ObsRO) measures to assess the patient experience of a condition or its treatment. However, a dyad approach where patients and caregivers can complete assessments together may be useful for assessing a shared treatment experience that may not be adequately captured by a PRO and/or an ObsRO. A systematic, targeted literature review of empirical literature was conducted to identify and describe published studies detailing dyad patient-caregiver outcome reporting approaches. The search was run in the MEDLINE®, Embase, and PsycINFO® databases using the OvidSP platform and was limited to English-language studies published within 10 years of the conducted search on 28 September 2021, and 13 articles were selected for full-text review based on pre-specified criteria. Advantages and disadvantages for use of a dyad data collection approach are discussed. Though not appropriate for all settings, dyad data collection may be useful for situations where the best practice approach to measurement does not capture all relevant perspectives, or the use of PRO and ObsRO also does not comprehensively capture all relevant concepts. In following, it may offer a pragmatic solution that can minimize the use of proxy assessment and limit missing data, particularly in research involving a shared patient and caregiver treatment experience. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Staff%20%26%20Provider%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.